Vitamin D Levels in Patients with Endometriosis Cysts - Mustikarani, Rianti; Mulyantoro, Inu (Journal of Biomedicine and Translational Research, 2025)
Background: Endometriosis is associated with lipid peroxidation by reactive oxygen species (ROS) which causes endometrial cell DNA damage. Vitamin D is known to have good antioxidant content, so it is thought to have the ability to inhibit proliferation, invasion and production of pro-inflammatory cytokines in endometriosis.Objective: To analyze the differences in vitamin D levels between endometriosis cyst patients and normal women and the relationship between vitamin D levels and the size of endometriosis cysts.Methods: Analytical observational study with cross sectional design with 60 samples consisting of 30 endometriosis cyst patients and 30 normal women. Evaluation was carried out on vitamin 25 (OH) D serum levels using the ELISA method and endometriosis cyst size. Cyst size is evaluated by assessing the largest diameter of a single endometriosis cyst assessed through an ultrasound examination by a specialist doctor.Results: Vitamin D levels in the endometriosis group were significantly lower than normal women (13.23 ± 5.39 ng/mL vs 15.83 ± 5.30 ng/mL; p = 0.048). Subjects with vitamin D levels <13.45 had a 4.03x (OR 4.03; CI95% 1.37-11.83) higher risk of experiencing endometriosis compared to subjects with vitamin D levels > 13.45 ng/mL. There was no correlation between vitamin D levels and the size of endometriosis cysts (p=0.720).Conclusion: Endometriosis patients have significantly lower serum vitamin D levels than normal women (OR 4.03; CI95% 1.37-11.83). Serum vitamin D levels do not significantly correlate with endometriosis cyst size.